2020
DOI: 10.1007/s00394-020-02416-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary patterns and prediabetes, undetected diabetes or clinically diagnosed diabetes: results from the KORA FF4 study

Abstract: Purpose Diet is one of the most important modifiable risk factors for the development of type 2 diabetes. Here, we aim to identify dietary patterns and to investigate their association with prediabetes, undetected diabetes and prevalent diabetes. Methods The present study included 1305 participants of the cross-sectional population-based KORA FF4 study. Oral glucose tolerance test (OGTT) measurements together with a physician-confirmed diagnosis allowed for an accurate categorization of the participants acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The results showed that there were differences in dietary patterns among patients with T2DM. The typical dietary characteristics of two dietary patterns in T2DM patients contained a variety of foods rich in quality protein such as soyabean products or whole grains and fewer intake of fruits and rice, which may be due to the transition to a low glycaemic index diet after diabetes considering their state of health, especially the reduction in the intake of foods that are likely to contribute to poor control of glycaemia (35,36) . Participants exhibiting adherence to the balanced pattern consumed moderate amounts of beneficial foods such as white meat, eggs, soyabean products and fresh vegetables tended to a Mediterranean diet, which was beneficial to stroke prevention (21)(22)(23)37) .…”
Section: Moderate Intake High Intakementioning
confidence: 99%
“…The results showed that there were differences in dietary patterns among patients with T2DM. The typical dietary characteristics of two dietary patterns in T2DM patients contained a variety of foods rich in quality protein such as soyabean products or whole grains and fewer intake of fruits and rice, which may be due to the transition to a low glycaemic index diet after diabetes considering their state of health, especially the reduction in the intake of foods that are likely to contribute to poor control of glycaemia (35,36) . Participants exhibiting adherence to the balanced pattern consumed moderate amounts of beneficial foods such as white meat, eggs, soyabean products and fresh vegetables tended to a Mediterranean diet, which was beneficial to stroke prevention (21)(22)(23)37) .…”
Section: Moderate Intake High Intakementioning
confidence: 99%
“…Some publications on German cohorts have equally demonstrated, that older adults are more likely to follow a healthier diet, characterized by lower consumption of meat or soft drinks and the highest intake of fish, vegetables, fruits, or whole grains in comparison with younger participants. [ 17,12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be mentioned that food groups are not consumed individually and do not reflect an individual's food choices. [ 12 ] Consequently, a breakdown of the main food groups into their subcategories would give more insights into which food components have higher health implications and are possibly associated with changes in the glycemic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both epidemiological and prospective studies indicate that chronic consumption of dairy exhibits a protective effect in preclinical populations. A diet including high consumption of dairy products show lower chances of having prediabetes, undetected diabetes, or prevalent diabetes, compared with a Western diet [ 70 ]. For individuals with prediabetes, a diet that includes dairy decreases postprandial glucose, insulin, and triglyceride response compared with a red meat/refined carbohydrate diet [ 71 ].…”
Section: Milk and Dairymentioning
confidence: 99%